South Coast appendicular mass management (SCAM) survey - Sajid, Muhammad S.; Ray, Kausik; Hebbar, Madhusoodhana; Riaz, Waleed; Baig, Mirza K.; Sains, Parv; Singh, Krishna K. (Translational Gastroenterology and Hepatology, 2019)
Background: Management of appendicular mass and interval appendicectomy remains a controversial issue. Recent publication of a randomized controlled trial (RCT) reported the incidence of around 20% neoplastic lesions in the age group of more than forty years among the interval appendicectomy group against magnetic resonance imaging (MRI) surveillance only which led to trial termination. The objective of this study is to evaluate the current practice of the management of appendicular mass in five major hospitals of South Coast of the England. Methods: A proforma was designed and emailed to the general surgical department of five hospitals in the South Coast of England. The proforma completion rate and compliance were improved by direct telephone call to the on-call registrars and consultants to collect data. Results: Fifty-three surgeons (22 consultants, 27 ST3–ST8 grade surgical trainees and 4 SAS grades) completed the proforma. The clinical, hematological and computerized tomography (CT) based diagnostic criteria, and in-patient intravenous antibiotics (IV ABTXs) in addition to the radiological drainage in amenable cases for appendicular mass/abscess were mostly agreed initial management plan among surgeons. Normalization of inflammatory markers and radiological resolution were agreed discharge indicators. Agreed follow up investigations were CT scan (by 23%), Colonoscopy (by 13%), and both CT and colonoscopy (by 57%) after discharging patients. Only 17% surgeons offered planned interval appendicectomy and 62% surgeons offered interval appendectomy in selective cases of appendicular mass within 6 weeks to 6 months after discharge. Conclusions: South Coast appendicular mass management (SCAM) survey confirms diverse practice to manage appendicular mass/abscess among surgeons working in South Coast hospitals. A substantial percentage of surgeons do not offer interval appendectomy to patients potentially leaving neoplastic lesions in situ.